A Pilot Study on the Effectiveness of Influenza Vaccination to Prevent Relapse of Steroid-Sensitive Nephrotic Syndrome in Children - Kumar, Pawan; Lanewala, Ali Asghar; Sanaullah, Agha; Ehsan, Afshan; Kashif, Saima; Zubair, Aasia (Infectious Diseases Journal of Pakistan, 2022)
Objectives: To study the effect of influenza vaccination in children with Steroid Sensitive Nephrotic Syndrome by comparing the frequency of viral Upper Respiratory Tract Infections (URI) and associated relapses from historic controls. Materials and Methods Trivalent, inactivated influenza vaccine (Influvac 2019/2020) was given to children with steroid-sensitive nephrotic syndrome before October 2019. They were either on low dose steroids or off medications and were observed for six months with recordings of their relapses and URIs. A comparison was drawn to the same number of unvaccinated children from the previous year. Results One hundred consecutive children were vaccinated. Five were lost to follow-up, so the effect on 95 children was compared with an equal number of unvaccinated children in 2018. The mean age of all the children was 4.7 ± 2.6 years (range 1-15 years) with a male to female ratio of 1.8:1. No immediate side effects or vaccine-related illnesses were seen in any patient. There were 17 episodes of URI in 16 (17%) children in the vaccinated group whereas 69 episodes in 59 (62%) children in the unvaccinated. Among the former, there were 55 episodes of relapses in 44 (46%) children while among the latter, there were 79 relapses in 71 (75%) patients. Both the number of URI episodes and relapses were significantly reduced in the vaccinated children (p <0.001). The odds of getting URI and relapse in them were 0.12 (95% CI 0.06-0.24) and 0.29 (95% CI 0.16- 0.54) respectively. No difference was seen in the number of relapses that were not associated with URI. Conclusion: There seems to be a significant decrease in all-cause URI and relapses in steroid-sensitive nephrotic children who are vaccinated with influenza vaccine. Further trials in larger cohorts are required to confirm the safety and beneficial effect of the recommended vaccination. Keywords: Steroid-sensitive Nephrotic Syndrome, Viral Upper Respiratory Tract Infections, Influenza Vaccine.